2022
DOI: 10.3390/foods11213493
|View full text |Cite
|
Sign up to set email alerts
|

Propionate and Butyrate Inhibit Biofilm Formation of Salmonella Typhimurium Grown in Laboratory Media and Food Models

Abstract: Salmonella is among the most frequently isolated foodborne pathogens, and biofilm formed by Salmonella poses a potential threat to food safety. Short-chain fatty acids (SCFAs), especially propionate and butyrate, have been demonstrated to exhibit a beneficial effect on promoting intestinal health and regulating the host immune system, but their anti-biofilm property has not been well studied. This study aims to investigate the effects of propionate or butyrate on the biofilm formation and certain virulence tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…16 Another mechanism is related to the downregulated expression of the invasion-associated gene in Salmonella Typhimurium when exposed to SCFAs. 15,36,37 Meanwhile, the levels of Bacteroidetes over Firmicutes were higher in the control diet mice, which has been reported to be associated with decreased susceptibility to the burdens of C. rodentium. 38 We also found that the abundance of Proteobacteria improved in HSD mice after infection, which has previously been reported to be associated with intestinal epithelial dysfunction.…”
Section: Discussionmentioning
confidence: 92%
“…16 Another mechanism is related to the downregulated expression of the invasion-associated gene in Salmonella Typhimurium when exposed to SCFAs. 15,36,37 Meanwhile, the levels of Bacteroidetes over Firmicutes were higher in the control diet mice, which has been reported to be associated with decreased susceptibility to the burdens of C. rodentium. 38 We also found that the abundance of Proteobacteria improved in HSD mice after infection, which has previously been reported to be associated with intestinal epithelial dysfunction.…”
Section: Discussionmentioning
confidence: 92%
“…However, more recent research reported an increase of acetic acid related to the colonisation of the specific strain Bifidobacterium breve BBG-001 in preterm neonates, but with no statistically significant difference on intestinal barrier function ( Fleming et al., 2021 ). More recent studies, such as the one performed by Liu et al. (2022) , indicated a decrease of Bifidobacterium subs.…”
Section: Short Chain Fatty Acid Producing Bacteria and Necrotising En...mentioning
confidence: 90%
“…SCFAs have been used in the agricultural industry because of their intrinsic broad-spectrum antimicrobial effect. Important examples in food production and human studies include the addition of butyric acid to control Salmonella ( Liu et al. 2022 ) and the ability of SCFAs to reduce the growth and virulence of pathogenic E. coli in a pH dependant manor ( Zhang et al., 2020 ).…”
Section: Other Functions Potentially Relevant For Preterm Infants At ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that butyric acid, one of the short-chain fatty acids, has the effect of inhibiting Salmonella [ 22 , 23 , 24 ]. Ruminococcaceae [ 25 , 26 ] and Lachnospiraceae [ 27 ] are important producers of butyric acid in the intestine. Studies have reported that the abundance of Ruminococcaceae and Lachnospiraceae in the intestinal tract of chicks infected with Salmonella is inversely proportional to the abundance of Enterobacteriaceae [ 18 ].…”
Section: Discussionmentioning
confidence: 99%